2012
DOI: 10.17795/compreped-6347
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Lipid Profile of Cord Blood in Neonates and its Correlation with Maternal Age in Iran

Abstract: A B S T R A C TBackground: Cardiovascular diseases (CVDs) are the leading cause of mortality in Iran; with dyslipidemia as an important contributing risk factor. Objectives: To assess the early onset of dyslipidemia, our goal was to determine lipids and lipoproteins levels in cord blood and their correlation with maternal age as a first study in Iran. Patients and Methods: This cross sectional study was done on the cord blood of 243 healthy, full-term newborn infants (114 females and 129 males). The blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
9
2
1
Order By: Relevance
“…In this study, the mean value of TG in 33% of females and 35% of males was higher than the 95 th percentile of triglyceride level reported in the Nelson textbook of Pediatrics, which indicates a high frequency of cord blood hypertriglyceridemia in our subjects (34). There are other reports of high cord blood hypertriglyceridemia in Iran (16,17,19,37), yet the level of cord blood TG in our study was higher than other reports from Iran (17,33). High triglyceride level may be due to the relatively high frequency of vitamin D deficiency in Iranian newborns (20,21).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In this study, the mean value of TG in 33% of females and 35% of males was higher than the 95 th percentile of triglyceride level reported in the Nelson textbook of Pediatrics, which indicates a high frequency of cord blood hypertriglyceridemia in our subjects (34). There are other reports of high cord blood hypertriglyceridemia in Iran (16,17,19,37), yet the level of cord blood TG in our study was higher than other reports from Iran (17,33). High triglyceride level may be due to the relatively high frequency of vitamin D deficiency in Iranian newborns (20,21).…”
Section: Discussioncontrasting
confidence: 85%
“…High triglyceride level may be due to the relatively high frequency of vitamin D deficiency in Iranian newborns (20,21). In our study there were no significant differences between the two sexes regarding the mean value of TC, LDL-C, HDL-C and TG, which is different from the results of some previous studies (17,27,37) and similar to the reports of Ghiasi et al (33). There was no statistically significant association between lipid levels and anthropometric parameters in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…9 Shahla Vaziri Esfarjani et al, studied the influence of maternal age on the cord lipid profile and found that there is a statistically significant negative correlation between cord blood HDL-C and maternal age (p <0.01). 10 A study by Juárez IE et al, concluded that there is an association between lipid levels in mothers and their children. 11 However, Murthy et al, in his study noted a significantly high level of TC in the newborn of mothers with high TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…This was in concordance with few other studies including Anderson et al and Tsang et al which showed no significant changes in the cord blood lipid profile in terms of gender. 12,13 However, LDL levels were higher in male newborns than female which is in contrast with study by Esfarjani SV et al 14 It is well-recognised fact that low Apo A1 and/or increased Apo B are associated with increased cardiovascular risk. Elevated Apo B levels and raised Atherogenic index (AI) in young adults are linked with cardiovascular disease in later life.…”
Section: Discussionmentioning
confidence: 84%